The Role of Other Major Postoperative Complications in Determining Outcomes of Acute Kidney Injury After Coronary Artery Bypass Surgery - Heitmann, Leon Arnar; Sveinsdottir, Nanna; Helgadottir, Solveig; Indridason, Olafur S.; Gudbjartsson, Tomas; Helgason, Dadi (Acta Anaesthesiologica Scandinavica, 2025)
Background: Acute kidney injury (AKI) is a common complication of coronary artery bypass surgery (CABG) and is associated with worse outcomes. It remains unclear whether AKIs impact on prognosis can be attributed to other concurrent major complications. Methods: This retrospective cohort study included consecutive patients undergoing isolated CABG at a single nationwide center from 2001 to 2020. Patients receiving preoperative dialysis and those with insufficient pre- and postoperative serum creatinine values were excluded. AKI and postoperative chronic kidney disease were defined by the serum creatinine component of the kidney disease: improving global outcomes criteria. Cox regression was used to estimate the impact of AKI on short- and long-term risk of mortality and major adverse cardiac and cerebrovascular events (MACCE); before and after excluding patients with other major complications. Propensity score matching was used to balance heterogeneity. Results: Out of 2287 individuals, criteria for AKI were met by 459 (20.1%), distributed as 375 (16.4%), 36 (1.6%), and 48 (2.1%) for Stages 1 through 3, respectively. The incidence of any major complication was 561 (24.5%), with 203 (8.9%) individuals having both AKI and major complications. Patients with AKI were older and had a higher incidence of comorbidities. AKI was associated with higher 30-day mortality (HR: 2.02, CI: 1.10–3.70) and inferior long-term outcomes (mortality, HR: 1.46; CI: 1.14–1.86; MACCE, HR: 1.48, CI: 1.20–1.81), but also predicted a higher hazard of postoperative chronic kidney disease (HR: 1.82, CI: 2.53–2.17). However, after excluding patients with other major complications, AKI was not associated with short- or long-term mortality but predicted inferior MACCE-free survival (HR: 1.59, CI: 1.23–2.06). Conclusions: AKI following CABG was not associated with short- and long-term mortality in the absence of major complications but predicted a higher risk of MACCE and postoperative chronic kidney disease. These results highlight AKIs role in progressive renal dysfunction and long-term cardiovascular morbidity, while its association with short-term mortality may be mediated by other major complications.
Publisher Copyright: © 2025 The Author(s). Acta Anaesthesiologica Scandinavica published by John Wiley & Sons Ltd on behalf of Acta Anaesthesiologica Scandinavica Foundation.